Trolley supermarket calculator / Muhammad Rafiq Papa Sule, Salheh Bajrai Husein Salim and Fatin Nurliyana Hanis Hasan Azhari - Papa Sule, Papa Sule; Husein Salim, Husein Salim; Hasan Azhari, Fatin Nurliyana Hanis (Universiti Teknologi MARA, Kedah, 2023)
Customers in supermarkets nowadays frequently do not consider the amount of money they are spending, which can lead to waste and financial problems in the future. We chose to develop a product called Trolley Supermarket Calculator because some customers don't even care about the total amount of items they put in their grocery cart, leading them to assume the pricing is still reasonable enough for them to pay. This trolley was created with modern technology that can count the total amount of items that users put inside their trolley. Customers can get benefits from using this product in a variety of ways, including reducing wasteful practices, making it easier for them to offer adequate money for payment, and planning to avoid the purchase of needless items. This product also has societal benefits, such as boosting community knowledge about the significance of financial control in spending. Our product comes with a variety of specialties too. We use a lightweight shopping trolley that is easier to handle and maneuver, allowing users to shop more comfortably in the supermarket. Remember that the shopping trolley follows the user from the moment they enter the supermarket until they leave. Furthermore, our products are designed for everyone. A number of clients are important, and the shopping trolley must be designed to accommodate people of various heights and ages. This can indirectly raise awareness among youngsters about the importance of smart financial planning. This trolley, also designed to be used from its four sides, allows one to make a purchase in a practical, manageable and accessible way. In addition, we would like to suggest customers to make a list of basic needs and wants before doing grocery shopping to reduce waste.